Window shopping ebook A novel. - Bailey, Tessa (2022)
USA TODAY BESTSELLER A sizzling, feel-good, opposites-attract holiday romance from Tessa Bailey, #1 New York Times bestselling author of It Happened One Summer—now in a beautiful new package! Two weeks before Christmas and all through Manhattan, shop windows are decorated in red and green satin. Stella is standing alone outside a famous department store, when a charming man asks her opinion on the décor. It's a tragedy in tinsel, she says, unable to lie. Then he asks for a better idea, with a twinkle in his eye. She didn't know he owned the place, when he put her on the spot, and now she's working for that man, trying to ignore that he's hot. But as a down-on-her-luck girl with a difficult past, Stella knows how to make a good opportunity last. So she gives it her all, working without stopping. Trying to resist temptation, because she's just window shopping.